PENGARUH PEMBEBANAN TERHADAP KOEFISIEN GRIP BAN TANPA BATIKAN PADA LINTASAN SEMEN SAAT KONDISI KERING DAN BASAH - YULIANTO, NURWAHID (2016)
LOADING EFFECT OF TIRE GRIP COEFFICIENT, WITHOUT PATTERN CEMENT ON TRACK WHEN WET AND DRY CONDITIONS Nurwahid Y, Pramuko IP.,Ir.,M.T, Bibit Sugito Ir.,MT. Mechanical Engineering University of Muhammadiyah Surakarta Jl. A. Yani TromolPos I Pabelan, Kartasura email : yuliantonurwahid6@gmail.com ABSTRACTION This study aims to determine the effect of loading on coefficient of tire grip on the cement track. This study uses artificial compound and compound the market as a comparison. The composition of the artificial compound consists of a mixture of raw rubber with chemicals that have not been vulcanized. Rubber used is natural rubber and synthetic rubber SBR RSS, while the chemicals used are plasticizers, fillers (fillers), anti-oxidants, accelerators, and other chemicals. In the artificial compound rubber mixing with chemicals is done by using a two-roll mixing with ± temperature of 55C. The mixing process begins mix of natural and synthetic rubber so that it blends and soft, then mix the chemicals to converge ± 30 minutes. The next process of vulcanization by using a mold-pressed part to a temperature of 160C for 15 minutes. Based on the results of tests performed, the amount of load that is used greatly affect the grip coefficient of the tire. Tests on artificial compound with dry conditions resulted grip coefficient of 0.665 load of 10kg, 13kg load 0.551, 0.531 15kg load, wet conditions resulted in 0,407 load 10kg, 13kg load 0.357, 0.334 15kg load. While in the market compound dry conditions produce a grip coefficient of 0.709 load 10kg, 13kg load 0.599, 0.572 load of 15kg and wet conditions resulted in 0.443 load 10kg, 13kg load 0.365, 0.340 15kg load. In testing the artificial compound shore A value of 68.333 and compounding market value of 60. Keywords: compound, loading, cement track, coefficient of grip